Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Pada Asosiasi Tenaga Ahli Kontruksi Nasional Sumut - Romauli Rumahorbo (JURIKOM (Jurnal Riset Komputer), 2019)
ATAKNAS North Sumatra in determining the best employee selection based on several assessment factors. The assessment factors consist of attitudes, absences, experience in the field of construction experts, attractive appearance, equivalent graduates, and able to improve good performance and be able to compete. For the sake of work effectiveness in performance appraisal, appropriate decision making is needed. Therefore, software is made that can make a decision to report on employee values. This software is built on the basis of a decision support system that has the ability to assess employee performance using the Multifactor Evaluation Process (MFEP) method. The MFEP method is a quantitative method that uses weighting systems. Decision making is done by giving subjective and intuitive considerations, weighing various factors that have an important influence on alternative choices.